Effects of nano CuO on aquatic decomposers: from community to cellular responses - Pradhan, Arunava (2012)
ntensive use of metal nanoparticles increases the chance of their release into freshwaters that may pose risk to biota and associated ecological processes. In streams, microbes play a key role in detritus foodwebs transferring carbon and energy from plant litter to invertebrate shredders. Here, we investigated the effects of nano CuO (<50 nm, nanopowder, Sigma) on aquatic detritus foodwebs by examining i) leaf-litter decomposition by bacterial and fungal communities, ii) cellular damage and physiological responses of fungal populations collected from non-polluted and metal-polluted streams, and iii) survival, growth and leaf consumption by an invertebrate shredder. Results were compared with those obtained with ionic copper. Stream-dwelling microbial communities were obtained by immersion of leaves in a non- polluted stream (Portugal). Microbial communities were exposed in microcosms to nano CuO (≤ 500 mg L-1) and Cu2+ (≤ 30 mg L-1). Leaf decomposition decreased with increasing concentrations of nano and ionic copper. Both copper forms reduced biomass of bacteria and fungi, and fungal reproduction. Cu2+ had stronger effects than nano CuO. Exposure to Cu2+ and nano CuO led to a decrease in fungal diversity and to shifts in species dominance. Increased concentrations of nano CuO (≤ 100 mg L–1) stimulated extracellular laccase activity by fungi. Populations from non-polluted streams were more affected by nano CuO than those from polluted streams, as shown by a stronger inhibition of biomass production, higher Cu adsorption, higher levels of reactive oxygen species and DNA strand breaks. Acute lethality tests suggested low toxicity of nano CuO to the shredder Allogamus ligonifer. However, sublethal concentrations of nano CuO (≤ 75 mg L–1) strongly reduced leaf consumption and invertebrate growth under aqueous and dietary exposure. Concentration of leached Cu2+ in the stream water increased with increasing nano CuO concentration. Exposure to 75 mg L–1 of nano CuO via water or food led to higher Cu adsorption and accumulation in larvae. Moreover, leached Cu2+ appeared to have a role in inducing toxicity of nano CuO.